Effect of pH on the growth of Bacillus sp in a culture medium with cane molasses (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
A large amount of commercial probiotics is offered to the aquaculture for the development of sustainable practices. One of the genera most usable in aquaculture as probiotic is Bacillus. The establishment of culture system for the Bacillus sp. Growth until optimal concentrations would allow its application as probiotic in the production of shrimp larvae, enhancing the survival and the quality of the final product. The aim of this work is to evaluate the effect of pH in the growth of Bacillus sp. in a culture medium with cane molasses. For the selection of the medium components were tested two bioassays with three replicates each one. The first bioassay was composed by cane molasses, rice dust, urea and sodium hydroxide as pH modulator. The second one had the same components, except for the cane molasses. Lately, nine experiments of the first bioassay were carried out for to test the relationship between bacterial concentration and pH. The range of pH varied among 4.2 and 5.8. The increasing of pH has a positive effect on growth of Bacillus sp. The culture medium composed by cane molasses, rice dust and urea stimulate the bacterial growth.
Keywords: Bacillus; cane molasses; probiotic; pH effect; bacterial growth